PENERAPAN IMPLEMENTASI BUDAYA DISIPLIN UNTUK MENCIPTAKAN IKLIM ORGANISASI YANG BERMUTU DI MIN 6 PANGANDARAN - Lilis Hermayati (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
The main research problem in this study is that the madrasa organizational climate is still not condusive. The employees’ discipline level is still low. Civilizing employee discipline is assumed can create an organizational climate quality at Madrasah Ibtidaiyah Negeri (MIN) 6 Pangandaran. This study aims to describe the implementation of a discipline culture in creating an organizational climate quality. This study used school action research. The subject in this study were teacher in Public Madrasa Ibtidaiyah (MIN) 6 that consists of five female teachers and six male teachers. The results showed that teachers’ discipline can improve the quality of organizational climate. The conclusions of this study are: 1) The quality of the organizational climate in MIN 6 Pangandaran before the implementation of the discipline culture is still low. 2) The process of implementing a discipline culture to create a quality organizational climate at MIN 6 Pangandaran increases in each cycle. The culture of teachers’ discipline increased well. It can be seen from the achievements of 75.54% in the first cycle to 85.09% in the second cycle. 3) The implementation of a discipline culture can improve the quality of the organizational climate at MIN 6 Pangandaran with an average score of 74.81% in the first cycle to 86.18% at the end of the second cycle. This study recommends that teachers should have the discipline to plan, implement, and evaluate performance so can produce the best quality of graduates.